Benefits of physical exercise for children and adolescents with cerebral palsy: a literature review - Paiva, Marcel dos Santos; Nardi, Marcia Galasso; Streiff, Tatiana Galante; Chamlian, Terezinha Rosane (Acta Fisiátrica, 2010)
There is strong evidence showing that the physical fitness and health of children and adolescents are substantially enhanced by frequent physical activity and, on the other hand, there are few studies that highlight the benefits of this practice in populations with disabilities or reduced mobility. Aiming to report changes generated by the application of physical exercise programs in children and adolescents with cerebral palsy (GMFCS levels I to III), focusing on the variables of strength, motor function, spasticity and quality of life, this literature review was carried out using MEDLINE, PubMed and Lilacs databases. In addition to using keywords in Portuguese and English to search for articles, papers were selected from a preliminary analysis following the criteria of inclusion by publication year, title and abstract analysis, excluding the review studies and systematic review. Out of the 8 studies included, only 3 randomly vary the sample amount studied between 8 and 65 individuals with cerebral palsy from the ages of 6 to 18. These studies contradict the paradigm that exercise, using weights for people with neurological disorders, can result in increased spasticity. This research also illustrates the benefits generated by increased muscular strength especially in the lower limbs through exercises using the overload principle. The results are favorable with regards to improvement in gross motor function as well as quality of life expressed in several factors such as increased motivation, participation in activities, socialization and self-perception.